Unveiling the role of stakeholder involvement for digital transformation of Indian food SMEs - Gupta, Sumit; Joshi, Deepika; Jagtap, Sandeep; Trollman, Hana; Verma, Virendra Kumar (Springer, 2025)
With the advent of digitalization, the economy of the world is quickly changing itself and Indian Small and Medium Enterprises (SMEs) are the front runners. This study sheds light on how digital transformation is crucial to support the growth, competitiveness, and sustainability in the present business environment, and how digital transformation is important to the SMEs in India. To encourage SMEs to take up digital technologies, the Government of India has been creating an environment that encourages such moves by launching several initiatives including Digital India, Make in India and Startup India. This paper studies the role of stakeholder involvement in digital transformation in Indian food SMEs. Structural Equation Modeling (SEM) is used on survey responses from 103 food SMEs using the Statistical Package for the Social Sciences (SPSS). From the findings, there is a close relationship between stakeholder involvement and technological advancement (β = 0.595, p < 0.001) and organizational and political factors (β = 0.709, p < 0.001) as viewed by leadership, which reflects multidimensional factors leading to digital adoption. However, stakeholder involvement does not have any significant effect on financial factors (β = 0.018, p = 0.87), financial constraints being a major barrier to transformation. Moreover, although technological advancement results in a positive effect towards digital transformation (β = 0.694, p < 0.001), organizational and financial challenges act as stumbling blocks altogether. In the case of managers, this study indicates proactive involvement of stakeholders, investment in employees upskilling and alignment of organizational goals with digital initiatives for the support of technology adoption. This information assists decision makers in estimating government incentives and public private partnerships to overcome financial constraints. Digital transformation for food sector SMEs depends on a coordinated support of stakeholders, policy and technological readiness as preconditions for long term competitiveness.
Keywords: Stakeholder's involvement; Digital transformation; Food SMEs; SEM; 3503 Business Systems In Context; 35 Commerce, Management, Tourism and Services; Stakeholder’s involvement; Digital transformation; Food SMEs; SEM